Mapping Coercive Violence - Monterrosa, Allison E. (Violence against women, 2023)
We conceptualize a new and distinct form of intimate partner violence: coercive violence. Coercive violence is a form of intimate partner violence in which the abuser intentionally engages in acts that expose his partner to state surveillance and violence at the behest of institutions or the state, including the child welfare system and the criminal legal system. Because the violence is perpetrated by an institution rather than an individual, it is difficult for the victim/survivor to seek justice or retribution. We conclude with suggestions for future research that interrogates coercive violence, its impacts on victims/survivors, and strategies for preventing it.